2020
DOI: 10.1111/dth.14342
|View full text |Cite
|
Sign up to set email alerts
|

Erythroderma: A clinicopathological study of 47 cases from 2018 to 2020

Abstract: Erythroderma, or exfoliative dermatitis, is an inflammatory disorder characterized by erythema and scaling, affecting most of the skin surface. It may be a result of many different causes such as previous dermatoses (psoriasis, eczema, atopic dermatitis [AD], pityriasis rubra pilaris, and pemphigus foliaceous), drug reactions, malignancies (mycosis fungoides [MF], Sézary syndrome, adult T cell leukemia/lymphoma), infections, and idiopathic disorders. Regardless of the etiology, the clinical appearance of eryth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 17 publications
5
12
0
Order By: Relevance
“…The mean age of affect study subjects in our study was 54.6 ± 23 years (range: 3-86 years, median: 61 years). In a retrospective study of 49 erythrodermic patients, the average age was reported to be 50.7 ± 17.9 years which was in concordance with our findings [4]. As an acquired-adulthood disease, erythroderma may have various underlying etiologies or may be idiopathic in at least 25% of 6…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The mean age of affect study subjects in our study was 54.6 ± 23 years (range: 3-86 years, median: 61 years). In a retrospective study of 49 erythrodermic patients, the average age was reported to be 50.7 ± 17.9 years which was in concordance with our findings [4]. As an acquired-adulthood disease, erythroderma may have various underlying etiologies or may be idiopathic in at least 25% of 6…”
Section: Discussionsupporting
confidence: 91%
“…Average age at the onset differs among various studies and reported to be 50.7 and 57 years in two recent reports respectively. 3,4 Even though skin involvement is the predominant clinical picture of the condition, life-threatening systemic complications such as tachycardia, electrolyte imbalance, edema and unstable body temperature may accompany [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a serious and potentially life-threatening systemic inflammatory skin disease, which progresses rapidly and has a long treatment cycle with mortality rate of 10%-20%. [1][2][3] This study aims to retrospectively analyze hospitalized patients with acquired immunodeficiency syndrome (AIDS) suffering from drug-induced erythroderma from January 2013 to December 2020 in the First Affi liated Hospital of Zhejiang University School of Medicine.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Erythroderma, a disease characterized by erythema with or without scaling over > 90% of body surface area, is a condition with high morbidity and mortality, which requires timely diagnosis and treatment. 3 Our study evaluated the diagnostic concordance and teledermatology impact on erythroderma diagnosis, investigations and treatment between referring hospitalists and the inpatient teledermatology teams at University of Pittsburgh Medical Center (UPMC).…”
mentioning
confidence: 99%